Show that satisfies the equation a(a+b)x 2 -b(a-b)x=(a-b) 2 ,and find the other value of x.

Show that  1962_20949_Capture.JPG satisfies the equation a(a+b)x2-b(a-b)x=(a-b)2,and find the other value of x.


1 Answers

Aman Bansal
592 Points
12 years ago

Dear Ritwick,


a(a+b)(a-b)2/a2 -(b(a-b)(a-b)/a)=(a-b)2



=a(a-b)(a-b)/a =(a-b)2


(a-b)/a +β = [b(a-b)]/[a(a+b)]

β = (a-b)[{b/a(a+b)} - 1/a]

therefore β = (b-a)/(b+a) 

Best Of Luck...!!!!

Cracking IIT just got more exciting,It’s not just all about getting assistance from IITians, alongside Target Achievement and Rewards play an important role. ASKIITIANS has it all for you, wherein you get assistance only from IITians for your preparation and winexciting gifts by answering queries in the discussion forums. Reward points 5 + 15 for all those who upload their pic and download the ASKIITIANS Toolbar, just a simple click here to download the toolbar….

So start the brain storming…. become a leader with Elite Expert League ASKIITIANS


Aman Bansal

Askiitian Expert

Think You Can Provide A Better Answer ?


Get your questions answered by the expert for free